2013
DOI: 10.4161/epi.25578
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus epigenetically affects genes predominantly involved in metabolic diseases

Abstract: (2013) Gestational diabetes mellitus epigenetically affects genes predominantly involved in metabolic diseases, Epigenetics, 8:9,[935][936][937][938][939][940][941][942][943]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
118
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(125 citation statements)
references
References 40 publications
4
118
1
2
Order By: Relevance
“…6,7 Data from animal studies also confirmed that in vitro embryo culture is associated with changes in DNA methylation. 6,8 Further, the fact that other conditions, e.g., intrauterine growth restriction (IUGR), which have an increased incidence in ART pregnancies, have been shown to demonstrate epigenetic alterations, [9][10][11] supports the hypothesis that epigenetic deregulation at non-imprinted CpG sites may also explain some of the medical issues associated with ART.…”
Section: Introductionmentioning
confidence: 77%
“…6,7 Data from animal studies also confirmed that in vitro embryo culture is associated with changes in DNA methylation. 6,8 Further, the fact that other conditions, e.g., intrauterine growth restriction (IUGR), which have an increased incidence in ART pregnancies, have been shown to demonstrate epigenetic alterations, [9][10][11] supports the hypothesis that epigenetic deregulation at non-imprinted CpG sites may also explain some of the medical issues associated with ART.…”
Section: Introductionmentioning
confidence: 77%
“…8,9 Among other studies, we have reported associations between maternal blood glucose concentrations at 2 nd trimester of pregnancy and fetal placental DNAm levels at the proximal promoter and intronic CpG island loci in the lipoprotein lipase (LPL) gene. 9 Considering that GDM had been repeatedly associated with a long-term increase in obesity risk and diabetes in offspring, our results have suggested that maternal hyperglycemia, through epigenetic modifications at LPL gene loci, could contribute to the fetal metabolic programming of chronic metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, it is essential to understand how LPL epigenetic perturbations could translate into later life changes in lipid metabolism, fat accretion, and growth.…”
Section: Introductionmentioning
confidence: 99%
“…In the Canadian cohort, DNA methylation was also measured at 485,000 CpG sites, using the Infinium HumanMethylation450 BeadChips platform (Ruchat et al, 2013b). CpGs in 3271 genes were found to be affected by maternal GDM.…”
Section: Reviewmentioning
confidence: 99%
“…Significantly, MEST gene DNA methylation was downregulated by 7 percentage points in GDM (N=80 GDM patients and 83 insulin-dependent GDM patients and N=57 controls). The authors also observed a significant decrease in blood MEST methylation (3 percentage points, N=37 obese patients and 37 controls) in adults with morbid obesity, supporting the idea that intrauterine exposure to GDM may have effects on the epigenome of the offspring throughout life.In the Canadian cohort, DNA methylation was also measured at 485,000 CpG sites, using the Infinium HumanMethylation450 BeadChips platform (Ruchat et al, 2013b). CpGs in 3271 genes were found to be affected by maternal GDM.…”
mentioning
confidence: 99%